Pembuatan dan Pendampingan Pengelolaan Website pada Pondok Pesantren Insan Mulia Baturaja - Defi Pujianto; Kadarsih Kadarsih; Satria Novari; Sri Hartati (Universitas Pahlawan Tuanku Tambusai, 2022)
The development of information technology, especially the internet, has a huge impact on the information that is conveyed through the website. To disseminate information, the cottage manager wants a website. However, the implementation of making a website requires expertise in its creation and management. For this reason, the manager of the boarding school encourages a thought so that the Islamic boarding school is able to create and manage their own websites that they need. Islamic boarding school managers need to make sure that their human resources have the expertise to make website applications as needed. Based on the problems above, PKM was held for the creation and assistance of the management of the Islamic boarding school website for Islamic boarding school operators. The target of this training is the operator of the noble Baturaja Islamic boarding school. This community service uses several methods, namely the method of making and assisting the use of the website. Through this service activity, it produces a website that can be accessed at https://insanmulia.pesantren.site. Through this PKM, operators can create and manage their own websites and parents and guardians of students can find out information, activities carried out in Islamic boarding schools.